The Influence Of Independence, Work Experience, Due Professional Care, Accountability, Integrity, And Clients Pressure On Audit Quality - Windhy Puspitasari; Astrid Mafela; Fithriana Melani (Universitas Trisakti, 2017)
This research aims to prove the influence of independence, work experience, due professional care, accountability, integrity, and client pressure. The respondent of this research is auditors that working at big four and non-big four Public Accountant Firms (KAPs) located in Jakarta, which is junior, senior, and manager position. The total respondents are 91. This research was conducted using a survey method. Data were collected by distributing questionnaires using convenience sampling. The data analysis used multiple regression. The results indicate that independence, work experience, due professional care, integrity, and clients pressure have a significant influence on audit quality. Since the mean score for all variable are not achieved Likert scale 3 or agree, for future research need to consider for distributing from senior auditor with experience for more than five years.